The Roles of Litigation - Stephen B. Burbank (Washington University Law Quarterly, 2002)
With all the attention in the media and in our legislatures, state and federal, to the supposed costs of civil litigation, it is important periodically to remind ourselves of its potential benefits. Moreover, as the Articles presented in this paper suggest, whether the question is costs or benefits, the responsible course is to seek data in preference to anecdotes and to recognize that data require sober interpretation (for which additional research may be required). The examined Articles also suggest that an appreciation of either the costs or benefits of litigation, as of the roles that it plays and should play, may be facilitated by, and in an increasingly interdependent world sometimes requires, a comparative perspective. Whether or not a desired change in litigation behavior finds support in documented experience, these Articles tell us that there are limits to the power of the judiciary to be the source of authority and, indeed, of the power of formal rules, whatever their source, to actually bring it about. The forces of personal and institutional self-interest are so strong in this country that one who calls for attention to facts in at least some forms of lawmaking may indeed be baying at the moon, while power is distributed so unequally that the messy, decentralized system in which we live may be our best protection against improvident change.
Keywords: Adversary system (Law); Social science research; Litigation